Contextual Rationality and Capabilities of Women Batik Businesses in Tanjungbumi, Bangkalan - Achmad Syarifudin; Sri Hidayati; Anik Andriani (UNIB Press, 2026)
Women batik businesses in Tanjungbumi Village, Bangkalan Regency, serve as important actors in maintaining cultural heritage while sustaining household economies. Despite the rapid expansion of digitalization, many of these entrepreneurs do not fully adopt contemporary marketing platforms such as Instagram or online marketplaces. Instead, they rely on WhatsApp and direct, relationship-based marketing. This study aims to examine the contextual rationality underlying these choices through Amartya Sen’s Capability Approach. Employing a descriptive quantitative design, the study involves all 49 women batik business owners in Tanjungbumi using a total sampling technique. The data analysis techniques used were preliminary inferential statistical analyses, including validity tests, reliability tests, and normality tests. The findings reveal that access to digital resources does not necessarily translate into enhanced capabilities, as not all actors utilize social media despite having the means. WhatsApp is preferred due to its perceived efficiency, familiarity, and ease of use within existing social networks. Furthermore, the functionings valued by these women include flexible working arrangements that accommodate domestic responsibilities while maintaining control over production and marketing processes. Importantly, resistance to full digitalization reflects a deliberate choice to preserve the quality of social interactions and trust-based relationships with buyers through direct transactions. These results demonstrate that economic decision-making among women batik entrepreneurs is shaped not merely by technological availability, but by contextually grounded evaluations of well-being, agency, and social relations. The study highlights the importance of understanding digital adoption through a capability lens that recognizes local values and lived realities.